Effect of Sugar Concentration on Gelling Properties of Pectin from Malaysian Banana Peels (Musa Acuminata × Balbisiana) - Chek Z. Hassan,; Siti. S. Ahmad,; Agbaje Rafiu,; S. Radhiah Omar (International Journal Of Innovative Science And Research Technology, 2024)
Gelation has sought to found every hydrocolloids’ function. Traditional method of pectin extraction from underutilized banana waste is significant in food industry to tackle the food security issue. The effect of sugar concentration (20.8%, 27.7%, 41.6% and 48.6%) on gels’ characteristics were investigated after the gel was efficaciously fabricated with the ratio of 1:08 (banana peel: water). For spreadability Line Spread assay, it was reported that increasing the percentage of sugar has decreased the distance of gel spread. There was a significant decrease (P<0.05) in the gel tenderness as the percentage of sugar increase. Similarly, the moisture content and water activity for gel were significantly reduced as the amount of sugar amplified at (p<0.05). All the four formulations showed a tremendous differences for color and texture analysis. From this study, this research managed to prove the capacity of pectin from banana peel in upholding the watermelon jam.